Polymerization of D,L-lactide in the presence of Boltorn™ polyester polyol - V. I. Gomzyak; N. V. Bychkov; A. S. Aduev; V. A. Ivanova; A. D. Koshelev; S. N. Chvalun (Тонкие химические технологии)
Objects. To synthesize monodisperse biodegradable hyperbranched polymers based on D,L-lactide in the presence of Boltorn™ H30 polyester polyol as a macroinitiator.Methods. 1H and 13C nuclear magnetic resonance (NMR) spectroscopy was used to study the chemical structure of the Boltorn™ H30 polyester polyol and (Boltorn™ H30)-PDLA hyperbranched copolymers. The molecular weight distribution of the polymers was studied by gel permeation chromatography (GPC). In order to study the thermal stability of Boltorn™ H30 polyester polyol, thermogravimetric analysis (TGA) was used. Polymerization of D,L-lactide was carried out in a block in the presence of Boltorn™ H30 polyester polyol.Results. The degree of branching of Boltorn™ H30 polyester polyol was calculated from NMR data, while the TGA method was used to determine the upper operational temperature range. The polymerization of D,L-lactide in the presence of Boltorn™ H30 polyester polyol used as a macroinitiator was studied. The molecular weight characteristics of the obtained copolymers were studied by NMR and GPC.Conclusions. Optimum conditions were determined for the polymerization of D,L-lactide when using Boltorn™ H30 polyester polyol as a macroinitiator. The possibility of synthesizing narrowly dispersed hyperbranched polymers (Boltorn™ H30)-PDLA under the described conditions was demonstrated.